2022
DOI: 10.1136/bmjopen-2021-059315
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of firearm injury: a cohort study of non-fatal firearm victimisation before and during the COVID-19 pandemic, Indianapolis, Indiana

Abstract: ObjectiveTo examine victimisation rates, geographic patterns and neighbourhood characteristics associated with non-fatal firearm injury rates before and during the COVID-19 pandemic.DesignA retrospective cohort study.SettingCity of Indianapolis, Indiana, USA, 1 January 2017–30 June 2021.ParticipantsIntentional non-fatal firearm injury victims from Indianapolis Metropolitan Police Department records. The study included information on 2578 non-fatal firearm injury victims between ages 0 and 77 years. Of these vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…Our study brings to light multiple significant findings related to the effects of the COVID-19 pandemic on pediatric firearm injuries. Consistent with multiple previous studies [ 8 , [11] , [12] , [13] , [14] , [15] , [16] ], pediatric firearm injury rates were found to have significantly increased during the pandemic compared to the five preceding years. While most previous studies on the topic do not include information on the intent or circumstances surrounding the shootings [ 8 , 11 , 12 , 14 , 16 ], we found that the escalation in pediatric firearm injuries was driven by a significant increase in pediatric firearm assaults/homicides.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our study brings to light multiple significant findings related to the effects of the COVID-19 pandemic on pediatric firearm injuries. Consistent with multiple previous studies [ 8 , [11] , [12] , [13] , [14] , [15] , [16] ], pediatric firearm injury rates were found to have significantly increased during the pandemic compared to the five preceding years. While most previous studies on the topic do not include information on the intent or circumstances surrounding the shootings [ 8 , 11 , 12 , 14 , 16 ], we found that the escalation in pediatric firearm injuries was driven by a significant increase in pediatric firearm assaults/homicides.…”
Section: Discussionsupporting
confidence: 90%
“…The relative decrease in unintentional pediatric firearm injuries that we discovered during the pandemic contradicts this theory, though the risks for firearm injury they point out are likely still accurate and significant. Our finding that pediatric firearm assaults/homicides significantly increased is likely still related in part to increased gun purchasing [ 8 , 11 , 13 , [23] , [24] , [25] ] and decreased youth supervision [ 8 , 14 , 16 ] associated with the COVID-19 pandemic. However, other factors such as COVID-19-induced economic crisis and subsequently increased neighborhood violence/crime rates may have played a more significant role in elevating pediatric firearm assaults/homicides.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations